Creation of automatic clamping mechanisms for spindle assemblies of machine tools using a formalized description of structural elements - Prydalnyi, Borys (Eastern-European Journal of Enterprise Technologies, 2022)
The characteristics of the functioning of automatic mechanisms for clamping workpieces and cylindrical tools in the spindle assemblies of metalworking machines determine the potential for improving the productivity and quality of processing. The conducted research is aimed at developing new approaches to the creation of automatic clamping mechanisms with qualitatively new and necessary characteristics of their functioning. The formation of new characteristics is achieved by implementing appropriate changes at the structural level of an object. The results obtained provide better opportunities for the development of structures of automatic clamping mechanisms by improving the systematization of a review of an increased number of alternative options for their structural elements. This was achieved by solving the problem of formal description and representation of structural elements operating on the basis of various physical effects within one subject area of the systematization matrix. The results allow strengthening the heuristic potential in the design and involving an extended range of physical effects suitable for effective energy transfer and conversion in the operating conditions of automatic clamping mechanisms. The possibility of describing structural elements as digital codes helps to increase the efficiency of analysis and processing of information of the initial design stages. Using the codes of the selected structural elements, three sequences corresponding to the structures of automatic clamping mechanisms according to the brief descriptions [1.7–2.4]–(1.1–2.3); [1.7–2.6]–(1.1–2.3); [1.7–2.6+1.6/1.7–2.1]–(1.1–2.3) were compiled. On their basis, designs of automatic clamping mechanisms with predictably better characteristics and extended technological capabilities are developed